How Can Interprofessional Skills Be Taught during University Studies? Student Teachers, and Social Work and Law Students Solving Complex Student Welfare Cases - Suvi Lakkala; Anna Nikupeteri; Lauri Lantela (MDPI AG, 2023)
This study focused on the learning of interprofessional skills through an interdisciplinary university course provided to student teachers, and social work and law students. This study explored the development of the course, the aim of which was to raise the student's understanding of interprofessional work to a more conscious level. The key research question was as follows: what kind of assignments and arrangements can be used to promote the interprofessional skills of students and their ability to solve complex student welfare cases? In this practice-oriented case study, we analyzed our own development process for the course, as well as the student's reflective essays. Through our analysis, we identified four central themes of an interdisciplinary course that can enhance interprofessional skills in students: (1) identifying discipline-specific expertise as a part of a multi-professional network; (2) gaining an understanding of interprofessional working processes; (3) realizing the complexity of student welfare cases; and (4) orienting towards working life. Our research demonstrates that building an interdisciplinary university course based on flipped learning principles, which incorporates collaborative and reflective assignments supported by various course materials and literature, can promote the learning of interprofessional skills and processes by students.